Differential Detection of Hepatic Metastases on 68Ga-DOTATATE PET/CT and 177Lu-DOTATATE SPECT/CT. (14th January 2023) - Zahed, Hanan; Beauregard, Jean-Mathieu; Abikhzer, Gad; Rush, Christopher; Probst, Stephan
Abstract: 68 Ga-DOTATATE PET/CT is indicated for selecting patients for peptide receptor radionuclide therapy (PRRT). Although highly sensitive, the detectability of smaller lesions, particularly in the liver, is lower. We present the case of a 58-year-old man with metastatic well-differentiated pancreatic neuroendocrine tumor whose MRI revealed progression of hepatic metastases. 68 Ga-DOTATATE PET/CT performed to determine eligibility for PRRT did not demonstrate DOTATATE-avid disease within the liver. 18 F-FDG PET/CT was also negative at the liver and the patient proceeded to 177 Lu-DOTATATE PRRT, where multi–time point posttherapy planar imaging and SPECT/CT showed intense uptake in the known liver metastases.